2020
DOI: 10.1016/j.xpro.2020.100094
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for In Vivo Evaluation and Use of Destabilizing Domains in the Eye, Liver, and Beyond

Abstract: SUMMARY Destabilizing domains (DDs) have been used successfully to conditionally control the abundance of proteins of interest (POIs) in a small-molecule-dependent manner in mice, worms ( Caenorhabditis elegans ), and Drosophila . However, development of such systems must account for delivery of the DD-POIs to the target tissue, accessibility of the target tissue to the small molecule, and quantification of stabilization. Here, we describe the considerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The DHFR DD system appears to be increasingly flexible with respect to diversity of model systems to which it can be applied (e.g., yeast ( Rakhit et al., 2011 ), mice, drosophila ( Kogenaru and Isalan, 2018 ), C. elegans ( Cho et al., 2013 )), the proteins it can effectively regulate ( Chen et al., 2020 ; Quintino et al., 2013 , 2018 ; Tai et al., 2012 ; Vu et al., 2017 ), and at the level of the small molecule pharmacological chaperone ( Peng et al., 2019 ; Ramadurgum et al., 2020a , 2020b ; Ramadurgum and Hulleman, 2020 ). With this increasing flexibility comes the ability to apply and fine-tune the DHFR DD system to achieve higher degrees of spatial (guided by AAV or virus tropism and/or a cell-type-specific promoter) and temporal (timing of small molecule administration and/or pharmacokinetic properties) control over protein abundance, and therefore cellular signaling—an exciting prospect for customizable or personalized gene therapy approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DHFR DD system appears to be increasingly flexible with respect to diversity of model systems to which it can be applied (e.g., yeast ( Rakhit et al., 2011 ), mice, drosophila ( Kogenaru and Isalan, 2018 ), C. elegans ( Cho et al., 2013 )), the proteins it can effectively regulate ( Chen et al., 2020 ; Quintino et al., 2013 , 2018 ; Tai et al., 2012 ; Vu et al., 2017 ), and at the level of the small molecule pharmacological chaperone ( Peng et al., 2019 ; Ramadurgum et al., 2020a , 2020b ; Ramadurgum and Hulleman, 2020 ). With this increasing flexibility comes the ability to apply and fine-tune the DHFR DD system to achieve higher degrees of spatial (guided by AAV or virus tropism and/or a cell-type-specific promoter) and temporal (timing of small molecule administration and/or pharmacokinetic properties) control over protein abundance, and therefore cellular signaling—an exciting prospect for customizable or personalized gene therapy approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional inducible gene regulation methods, such as tetracycline/doxycycline-based transactivation systems (i.e., Tet-On ( Gossen et al., 1995 ) and Tet-Off ( Gossen and Bujard, 1992 )), require an extended time frame to activate and reverse because of additional processing time of transcription and translation to reach expected protein levels and prolonged deposition of the regulating molecule ( Au - Gomez-Martinez et al., 2013 ; Das et al., 2016 ; Sun et al., 2007 ). In contrast to transcriptionally regulated conditional systems, protein-based regulation approaches such as the Escherichia coli dihydrofolate reductase (DHFR) destabilized domain (DD) system ( Iwamoto et al., 2010 ) can directly and conditionally regulate abundance at the protein level after addition of trimethoprim (TMP) ( Iwamoto et al., 2010 ; Sellmyer et al., 2012 ; Vu et al., 2017 ) or a TMP-like molecule ( Peng et al., 2019 ; Ramadurgum et al., 2020a , 2020b ). Such a system is especially useful when expressed transgenes are potentially toxic if expressed for prolonged periods of time, or when spatiotemporal regulation is required, such as in the case of particular stress-responsive signaling pathways which typically occur in a sinusoidal-like manner ( Datta et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ten-week-old WT C57BL/6 mice were anesthetized with a ketamine/xylazine cocktail (120 mg/kg and 16 mg/kg, respectively) followed by application of tropicamide (dilator, 1%[w/v]) (Alcon, Fort Worth, TX), and GenTeal Severe Dry Eye Gel (Alcon) to maintain ocular hydration. Injections were performed on a stereo microscope (Zeiss, Oberkochen, Germany) using a 33G 1/2” needle attached to a Hamilton micro-syringe (Hamilton, Reno, NV) containing 1 μL AAV (1×10 11 vg/mL), or HBSS-T vehicle control as described previously in greater detail 33 . The eye was proptosed, and punctured above the limbus with a 27G needle, followed by slow injection of the virus into the puncture site at a 45° angle.…”
Section: Methodsmentioning
confidence: 99%
“…to maintain ocular hydration. Injections were performed on a stereo microscope (Zeiss, Oberkochen, Germany) using a 33G 1/2" needle attached to a Hamilton micro-syringe (Hamilton, Reno, NV) containing 1 L AAV (1x10 11 vg/mL), or HBSS-T vehicle control as described previously in greater detail 33 . The eye was proptosed, and punctured above the limbus with a 27G needle, followed by slow injection of the virus into the puncture site at a 45° angle.…”
Section: ∆∆𝐺 ∆𝐺 ∆𝐺mentioning
confidence: 99%
“…In addition to reversibility and tunability, the drug-dependent stabilization of the target protein is an important feature of the DD technology. It has been shown that the DD approach works in several organisms [42][43][44][45][46][47]. Although this is useful for the study of constitutively active enzymes, etc., it requires the continuous exposure of the stabilizing ligand to the cells, for protein expression.…”
Section: Small-molecule-switchable Degronsmentioning
confidence: 99%